Between altruism and commercialisation: some ethical aspects of blood donation - Carlo Petrini (Istituto Superiore di Sanità, 2013)
Numerous documents (declarations, codes, recommendations, guidelines) issued by eminent institutions recommend that the donation of blood should be voluntary and unremunerated. This does not preclude the possibility: 1) that donors receive some form of reimbursement; 2) that subsequent procedures, which inevitably incur costs, may involve considerable financial activity; 3) that legislation in some nations may allow trade in certain types of human biological material; 4) that voluntarily donated human blood be used to derive products that are subsequently marketed. The present article highlights some of the contradictions generated by these considerations and affirms that they do not undermine the primary duty to uphold the voluntary nature of donation.